The efficiency wages Phillips curve: Closed economy versus open economy - Andrea Vaona (Kiel Institute for the World Economy (IfW), 2011)
The paper extends the efficiency wages Phillips curve from a closed economy context to an open economy one with both commodity trade and capital mobility. Opening the trade account does not alter the slope of the Phillips curve, but it makes its position a function of the change of foreign and domestic outputs. Opening the capital account also alters the slope of the Phillips curve.
Keywords: E3; E20; E40; E50; 330; Efficiency wages; money growth; Phillips curve; inflation; Phillips-Kurve; Effizienzlohn; Offene Volkswirtschaft; Theorie